Not Like Us: Imagining Meaning in Syntactic Presence and Absence of The To-Be Verb - Simanjuntak, Agnes Pebriananda (Metahumaniora, 2026)
A sentence consists of a deep and surface structure that each structure could contain different propositions in which it is used to transfer meanings to the addressee. This study examines the syntactic structure of a song lyric entitled Not Like Us, which was sung by Kendrick Lamar, to analyse the meanings conveyed in the sentences expressed with ungrammatically accepted structure. This research is conducted using a qualitative method where sentences in every line of the lyrics are analysed in terms of the presence and absence of the to-be verb. This study aims to categorize the use of to-be verb in the song Not Like Us and find the implied meaning found in sentences with both the syntactic presence and absence of the to-be verb. This research argues that the absence of the to-be verb is a communicative way to convey a particular meaning, rather than being considered an ungrammatically accepted structure. The result of this study concludes that word arrangement in song lyrics conveys meanings differently depending on the use of English grammar and syntactically unaccepted grammar.